Investigating blended learning and its influence on academic self-efficacy of university students a phenomenological investigation - Aves, Ceasar Steve; Jusay, Marion Angelique; Melo, Yanka Denise; Rudas, Michaela Shaneil
Findings revealed that several factors in a BL set-up significantly affect their perceived ASE. BL has also positively impacted and increased ASE compared to pure remote learning. Overall, it indicates that a well-thought and well-executed blended learning implementation can significantly increase students' academic self-efficacy and improve their experience.